2018
DOI: 10.24815/siele.v5i2.8943
|View full text |Cite
|
Sign up to set email alerts
|

The shift of Acehnese language: A sociolinguistic study to preserve regional languages

Abstract: This study uses a case study research method with a qualitative study design. The aims of the study were to find out the domains of Acehnese language shifts in Langsa and the reasons why Acehnese teenagers are shifting their language. Five districts in Langsa, one of the cities in Aceh, Indonesia, became the research location. They were Langsa Kota, Langsa Barat, Langsa Timur, Langsa Baroe and Langsa Lama. The respondents were Acehnese young adults within the age range of 18 to 21 years old. There were 10 resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…in their daily communication (Paauw, 2009, Kustati, 2014 as a form of their existence, ethnic and cultural identity (Yusuf, Aziz & Kamarullah, 2017), whether they live in rural or urban areas. The local languages they use may occur in their neighborhood, place of work, school, or elsewhere (Aziz, et al, 2017;Chaer, 2007;Ulfa, Isda & Purwati, 2018). Besides, there is a tendency to maintain the language of each region without leaving the use of Indonesian as the national language (Aziz, et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…in their daily communication (Paauw, 2009, Kustati, 2014 as a form of their existence, ethnic and cultural identity (Yusuf, Aziz & Kamarullah, 2017), whether they live in rural or urban areas. The local languages they use may occur in their neighborhood, place of work, school, or elsewhere (Aziz, et al, 2017;Chaer, 2007;Ulfa, Isda & Purwati, 2018). Besides, there is a tendency to maintain the language of each region without leaving the use of Indonesian as the national language (Aziz, et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Al-Auwal (2017), found that the Acehnese language is only used in homes and in villages. This point is supported by research from Ulfa et al (2018). Ulfa et al (2018), found that in Acehnese language, there is also a language shift.…”
Section: Introductionmentioning
confidence: 65%
“…Ulfa et al (2018), found that in Acehnese language, there is also a language shift. The language shift occurred from Acehnese to Indonesian in the domains of education and friendship (Ulfa et al, 2018).…”
Section: Introductionmentioning
confidence: 98%
“…The borrowed alternative availability is suspected of what made most words become archaic in the current and previous studies. The status of Acehnese is now even more threatened because bahasa Indonesia has been dominantly used by the young generation (Ulfa, Isda, & Purwati, 2018), and more parents have stopped speaking Acehnese to their children. The result of data analysis of Acehnese archaic words in Hikayat Prang Sabi shows that there are five archaic words and 49 semi-archaic words.…”
Section: Resultsmentioning
confidence: 99%